The vitreous refugee - Lintner, Claudia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
Taking the example of smartphones, the article discusses the impact of digital technologies on refugee trajectories considering the ambivalent potential of technologies to generate simultaneously new opportunities for refugees’ agency and new structural constraints regarding their mobility and actions due to control capacities. It therefore aims to offer a deeper discussion of the empowerment-control nexus and promote a better understanding of the various intersections that are developing between digitalization and migration/mobility patterns. The article is based on a qualitative research approach. Linking the individual level (the need of refugees to use smartphones for communication, information and orientation) to the political level is an emerging international market of surveillance and security technologies that has developed in recent years. Technology firms have contributed to develop and to promote the digital turn in surveillance and security-focused practices based not exclusively on the physical body, but on the digital devices as ‘extended bodies’.